Problems of use of fingerprint information in the investigation of crimes - Логвиненко, Аліса Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article examines some of the problems of using fingerprint information in the process of detection, investigation and prevention of crime. Characterized in detail the stages of fingerprint examination. The article analysed modern scientific views and ways of development and improvement of fingerprinting. In forensic science one of the earliest is traces of the doctrine of human hands, given the origin and history of use in the detection and investigation of crimes. Study of fingerprint knowledge, especially in their use of a pre-trial investigation enable to select individual events, describing the main features of the formation of this important section of forensic science and necessary activity that contributes to the detection and investigation of crimes. Obviously, fingerprint traces, as a reflection of morphological features hands and skin relief and unique features of papillary patterns, their uniqueness, individuality and immutability has long been interested in mankind. The current state of criminalistics, held in its development long way from its disparate formerly separate branches to the system of scientific knowledge before high levels of integrated implementation of the purposes of justice of scientific and technological progress, the deep development of methodological problems, tactics and methods of crime investigation. Today forensics enables high accuracy to identify the footsteps of palms or fingers. Traces of hands, which were found at the scene, is irrefutable proof that a person was at this place. One of the most critical problems is to ensure the quality of pre-trial investigation. The main purpose is scientific support for forensic practice of pre-trial investigation against crime. I must say that prompt and full disclosure of crimes is achieved during the pre-trial investigation. Using achieve natural and technical sciences, studying and summarizing good practice solving crimes, criminologists, create new, more sophisticated methods and means of fighting crime.